Pengaruh Waktu Pemeraman Terhadap Nilai Kuat Tekan Bebas Dan Permeabilitas Tanah Lempung Yang Dicampur Dengan Semen Dan Abu Ampas Tebu - Kosat, Bruno Rikardo Nahak; Lebang, Fauzy; Setiawan, Amran (Jurnal Penelitian Teknik Sipil Konsolidasi, 2023)
Soft clay has a relatively low subgrade bearing capacity and relatively large subgrade compression and lasts for a relatively long time so that it becomes a major problem in the development of transportation infrastructure. One of the efforts to improve soft clay soil is by adding bagasse ash and cement as a stabilizing agent on the soil. The research aims to determine the curing time on the value of unconfined compressive strength in clay soil after adding bagasse ash and cement, the permeability value of clay soil after adding bagasse ash and cement and the comparison value of unconfined compressive strength with curing time. This study used a variation of 0%,5%,10%,15% of palm bunch ash and cement by 5% of the dry weight of the soil. The test results of the free compressive strength value with a curing time of 0 days at 5% Cement + Sugar Bagasse Ash 0%, 5%, 10%, and 15% there was an increase and decrease in the value of the free compressive strength (Qu), in this case the highest Qu was in the variation cement 5% and bagasse ash 10% with a curing time of 14 days an increase in cohesion value of 0.716. The permeability coefficient increases with the increase in the percentage of bagasse ash with a fixed percentage of cement. With an average increase in the coefficient of permeability of 0.0149.